The effect of cigarette smoking on early osseointegration of dental implants: a prospective controlled study - Bezerra Ferreira, José Divino; Rodrigues, Jose Augusto; Piattelli, Adriano; Iezzi, Giovanna; Gehrke, Sergio Alexandre; Shibli, Jamil Awad (Clinical oral implants research, 2016)
Objective This study evaluated the effect of cigarette smoking on the percentage of early bone‐to‐implant contact (BIC%), the bone density in the threaded area (BA%) as well as the bone density outside the threaded area (BD%) around micro‐implants with sandblasted acid‐etched surface retrieved from human jaws. Material and methods Twenty‐two subjects (mean age 55.4 ± 4.5 years) were divided in two groups: smokers (n = 11 subjects) and never‐smokers (n = 11 subjects). Each subject received one micro‐implant during conventional mandible or maxilla implant surgery. After 8 weeks, the micro‐implants and the surrounding tissue were removed and prepared for histomorphometric analysis. Results Two micro‐implants placed in smokers showed no osseointegration. Early stages of maturation of the newly formed bone were present, mainly in the never‐smokers. Marginal bone loss, gap, and fibrous tissue were present around some implants retrieved from smokers. Histometric evaluation indicated that the mean BIC% ranged between 25.9 ± 9.1 and 39.8 ± 14.2 for smokers and non‐smokers, respectively (P = 0.02). Smokers presented 28.6 ± 10.1 of BA% while never‐smokers showed 46.4 ± 18.8 (P = 0.04). The mean of BD% ranged between 19.1 ± 7.6 and 28.5 ± 18.8 for smokers and never‐smokers, respectively (P = 0.21). Conclusion Cigarette smoking has a detrimental effect on early bone tissue response around sandblasted acid‐etched implant surface topographies.